PENERAPAN METODE TWO STAY TWO STRAY BERBANTUAN KARTU KUARTET UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV - Ayu Ghinadi; Diana Setiana; Abdul Karim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the learning outcomes of fourth-grade students in the subject of Citizenship Education (PKn) at SD Negeri Simaja through the implementation of the Two Stay Two Stray (TSTS) method assisted by quartet card media. The issue raised is the low learning outcomes and lack of student activity caused by conventional teaching methods. This research is a Classroom Action Research (CAR) conducted in two cycles with a total of 23 student subjects. Data collection techniques were carried out through tests, observations, and documentation. The research results show a significant improvement in student learning outcomes. In the pre-cycle stage, only 8 out of 23 students (34.78%) achieved the Minimum Completeness Criteria (KKM). In cycle I, the number increased to 15 students (65.21%), and in cycle II, 20 students (86.95%) achieved KKM, resulting in an increase of 52.17% from the initial condition. These findings indicate that the application of the TSTS method assisted by quartet card media is effective in improving learning outcomes and student engagement in civic education. This method encourages interaction, active participation, and a deeper understanding of the material. Thus, this approach can be recommended as a learning strategy to improve the quality of Citizenship Education learning in elementary schools.